Peran ai dalam kepemimpinan di era digital: prespektif qs an-nisa’ ayat 58 - WAFA’, MOH. ’UFAIR NASHIRUL (Maliki Interdisciplinary Journal, 2026)
Technological developments in the 21st century are rapid and have brought significant changes to various aspects of life, including governance. One innovation that has attracted considerable attention is artificial intelligence (AI), which has begun to be applied in state administration. This phenomenon culminated in Albania officially appointing an AI system named Diella as minister for corruption and public procurement in September 2025. This phenomenon has sparked discussions about trust in AI, which lacks reason, conscience, and moral responsibility to carry out leadership mandates in accordance with the principles emphasized in the Qur’an. The purpose of this article is to analyze the role of AI in leadership in the digital era using a thematic interpretation approach to Qur’anic verses related to mandates and leadership. The research findings indicate that the Qur’an considers leadership as a mandate related to ethical, spiritual, and sharia-compliant aspects, which cannot be represented by non-human entities. Therefore, the role of AI in leadership should only be as a tool, not as the primary power holder in government.